Evaluating knowledge, skill and attitude of PG Diploma in Inland Fisheries and Aquaculture Management graduates - Bhavana B; Shivaji Argade; Pailan G. H.; Singh D. K; Neha W Qureshi (Journal of Indian Fisheries Association, 2023)
The evaluation of skill development programs helps to improve training programs’ effectiveness for its wider adaptability. The present study evaluated the knowledge, skill and attitude of selected PGDIF&AM (Post Graduate Diploma in Inland Fisheries and Aquaculture Management) trainees. The knowledge-skill index and attitude scale were developed for evaluating the same. The majority of trainees perceived medium knowledge and skill gain after completion of the course. The knowledge (0.63) gain was predominantly high as compared to skill (0.57) gain among PGDIF&AM trainees. The majority (61.33%) of the trainees showed a low to moderately favourable attitude towards PGDIF&AM course. The attitude of trainers (0.77) was found highly favourable towards the PGDIF&AM course as compared to their attitude (0.68) towards teaching methods (p=0.030). Trainees expressed their concerns about the course content and teaching methods which need to be addressed on priority basis for making learning more effective and compatible with their job profile. The eligibility criteria and structure of the PGDIF&AM course needs to be revised through strategic interventions for its wider reach and applicability.